Early diagnosis of prostate cancer among 1181 patients attending an urology outpatient department - (:unkn) unknown (My University, 2000)
Purpose: Prostate cancer (PCa) represents the most common malignancy in males and the second leading cause of cancer deaths. There is no effective treatment for metastatic disease, while definite treatment of organ-confined disease is available. Therefore, early diagnosis is essential for PCa. In this study, early diagnosis of PCa based on the combination of prostate specific antigen (PSA) and digital rectal examination (DRE) in patients attending the urology outpatient department owing to lower urinary tract symptoms was assessed. Patients and methods: A total of 1181 consecutive patients who attended our outpatient department with lower urinary tract symptoms are enrolled in this study. Patients with elevated serum PSA level (> 4 ng/ml) and/or abnormal DRE underwent transrectal ultrasound (TRUS) guided biopsy. Results: A total of 564 patients with a PSA value less than 4 ng/ml and normal DRE were included in a surveillance program consisting of annual follow up with PSA and DRE. PCa was detected in 132 (21.3%) of the remaining 617 patients who underwent TRUS-guided systematic and lesion-directed biopsies. In the PCa group, clinically localized disease was found in 68 and metastatic disease in the remaining 64 patients. In the clinically localized group, 5 patients were included in a surveillance program, 5 patients were referred for radiotherapy, 19 patients had combination therapy (hormonal+radiotherapy) and the remaining 39 patients underwent radical retropubic prostatectomy. In the surgery group, 22 patients were found with stage pT2N0 and 17 patients pT3N0 disease. Thus, the incidence of clinically and pathologically organ-confined prostate cancer in the outpatient population with prostatism symptoms was 5.7% (68/1181) and 1.9% (2/1152), respectively. Conclusion: Pathologically non-organ confined PCa accounts for 44% (17/39) of clinically localized cases and nearly half of all PCa cases are metastatic, indicating that there are still problems in the early diagnosis of PCa when definite treatment is still possible.
Keywords: Definite treatment; Digital rectal examination; Early detection; Prostate cancer; Prostate specific antigen